MEKANISME HUKUM DAN PENYELESAIAN SENGKETA TERHADAP LALU LINTAS PEMBAYARAN LUAR NEGERI DALAM KEGIATAN EKSPOR IMPOR - Prawitra Thalib (Jurnal LEX SPECIALIS, 2010)
Economic activity is a vital point not only for a person but also a nation, this is caused by the urgency of economic aspect to increase fund and wealth as well, the source of economic activity is a trade, because trade will make money roll faster and it will give benefit in every aspect include public and privat aspect, in this era trade activity not only based on nation or continent but it is expanded into inter-nation and inter-continent or in the other word is international, the great scale in trade activity is create a new issue, because a few people is try to violate the other person in trade activity especially in great scale like inter-nation, in this case due process of law is needed to ensure trade activity is going good as well and to reduce jeopadize in international economic activity. Key Note : Due process of law in export import activity